Attitudes and Beliefs of Older Female Breast Cancer Survivors and Providers About Exercise in Cancer Care. - Perry, Cynthia K.; Ali, Wafaa Bin; Solanki, Emma; Winters-Stone, Kerri (Oncology Nursing Forum, 2020)
OBJECTIVES: To understand breast cancer survivors' and providers' attitudes and beliefs regarding exercise counseling and structured exercise programs within cancer care. SAMPLE & SETTING: 61 female breast cancer survivors and 11 breast cancer providers from a university cancer center in the Pacific Northwest. METHODS & VARIABLES: Survivors completed anonymous self-report surveys, and providers participated in semistructured interviews. Survey data were analyzed using descriptive statistics, and interview transcripts were analyzed using qualitative content analysis. RESULTS: Breast cancer survivors and providers believed that including exercise counseling within cancer care was important. More than half of the survivors reported that they would attend structured exercise classes; a majority of providers thought cancer centers should offer exercise programs. IMPLICATIONS FOR NURSING: Nurses could facilitate exercise counseling within cancer care and advocate for clinic-based exercise programs.